Wider Economic Benefits of Investments in Transport Corridors and the Role of Complementary Policies - Melecky, Martin; Sharma, Siddharth; Subhash, Hari (World Bank, Washington, DC, 2018)
This paper estimates the impact of the Golden Quadrilateral and North-South-East-West Highways in India on welfare, social inclusion, and environmental quality. The analysis uses district-level data for 1994-2011 and the difference-in-difference method. The results suggest that the highways shifted employment from the farm to the nonfarm sector, and that this shift was accompanied by an increase in output per capita. However, there is no evidence of an impact on household expenditure per capita, the poverty rate, or the incidence of regular wage employment. The results suggest that the highways caused an increase in air pollution. The effects of the highways are heterogeneous, depending on conditions in local factor and product markets.